Implementation of Social-Emotional Learning Approach in Religious Education To Enhance Student Learning - Lukas Lui Uran (FKIP, Universitas Palangka Raya, 2025)
Social and emotional learning (SEL) is an engaging and enjoyable method within the teaching and learning process. This approach is based on the understanding that academic success alone is insufficient to support students’ holistic development. One of the factors contributing to low learning motivation among students is the lack of implementation of social-emotional learning strategies in the classroom. This study aims to examine how the application of social-emotional learning in Catholic Religious Education influences student learning motivation. The research employed a quantitative method using a quasi-experimental design. The subjects were Grade 10 students at St. Joseph Catholic Vocational High School (SMK Katolik St. Yosef Nenuk). A total of 15 students from the Automotive Engineering class formed the experimental group, while another 15 students from the Building Construction and Computer Networking classes were assigned to the control group. The sample was selected using purposive sampling. Data were collected through questionnaires and documentation, then analyzed using an independent two-sample t-test to test the hypothesis. The results showed a significant difference in student motivation between those taught with SEL and those taught with conventional methods. This is evidenced by a t-test significance value of 0.000, which is less than 0.05. In other words, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. These findings reinforce that social-emotional learning is more effective than conventional teaching methods in increasing student motivation, particularly in Catholic Religious Education